Effect of Liquid Microbial Consortium on Physio Chemical Properties of Rice Field (Oryza Sativa) in a Vertisol - , Dungsi Nabum, Rakesh Banwasi, Temsusangla I. Jamir (Archives of Current Research International, 2024)
A study was conducted during kharif 2020 on "Effect of liquid microbial consortium (Azotobacter, Azospirillum, PSB (Pseudomonas mallei, Pseudomonas cepaceae, Penicillium sp.) and KSB) on physio chemical properties and microbial population of rice field (Oryza sativa) in a Vertisol" at the Indira Gandhi Krishi Vishwavidyalaya's Research cum instructional farm in Raipur (C.G.). Experiment included seven treatments viz. control (no fertilizer, no liquid NPK microbial consortia), two independent applications of 75 % RDF (90:45:30) and 100% RDF ((120: 60: 40) N, P2O5, and K2O kg ha-1 and four various combinations of seed and soil application of liquid NPK microbial consortia. Seed coating with NPK consortia @5ml kg-1, with 75% and 100% RDF and Seed coating with NPK consortia @5ml kg-1 + Soil application of NPK consortia @3 L ha-1 at 21 DAS with 75%RDF and 100%RDF. In the experiment, liquid biofertilizer products, such as liquid microbial NPK consortia were used. The population of Azotobacter, Azospirillum, phosphorous solubilizing bacteria (PSB), potassium solubilizing bacteria (KSB) and total bacterial population were significantly influenced by application of consortia as seed treatment @ 5ml kg-1 only and by a combination of seed treatment @ 5ml kg-1 seed + soil application @ 3 L ha-1 at 21 DAT with 75 or 100 % recommended dose of fertilizers and showed statistically significant higher microbial population in comparisons with the treatments of untreated alone applications of 75 or 100 % RDF. The results showed that the soil reaction, (pH) salt concentration (Electrical conductivity) and organic carbon status were not significantly influenced by the different treatments of fertilizer levels and microbial consortia applied. Slight decrease in the soil reaction (pH) and slight increase in the OC status after the harvesting of rice were observed from their initial soil values (before application of treatments). It might be due to the addition of organic matter as plant residues (straw and roots) of rice crop gown in the field. As compared to untreated- control (T1) a slight decrease in pH and increase in organic carbon content due to application of fertilizer and microbial consortia were also recorded. The residual available nitrogen in the soil after the harvesting of rice was not significantly influenced by the fertilizer levels and NPK consortia applied. The initial status of the experimental soil was low for available nitrogen (224 kg ha-1), medium for available phosphorus (24.5 kg ha-1) and high for available potassium (384 kg ha-1). Due to the addition of nitrogen through the fertilizer (90-120 kg ha-1) and less uptake of native nitrogen from the soil, a marginal increase in the residual available N in the soil from the initial level was observed in all treatments except the control (no fertilizer, no consortia). The residual status of available potassium was also not significantly influenced by the applied fertilizer doses and NPK consortia. A marginal decrease in the residual available K status after the harvesting of rice was observed in all treatments. A decrease was found in the control plot. A decrease in the K status (from the initial level) was observed less where a full dose of NPK fertilizers (100%) was applied with the NPK consortia. Ramlakshmi et al. [1], also observed slight reduction in soil pH and increase in organic carbon content in biofertilizer inoculated treatments as compared to the un-inoculated control soil [2].